A low-coordinate platinum(0)-germylene for E–H bond activation and catalytic hydrodehalogenation - Sonia Bajo; Enrique Soto; Marta Fernández-Buenestado; Joaquín López-Serrano; Jesús Campos (Nature Communications)
Abstract Pairing transition metals and heavier tetrylenes (Si, Ge, Sn, Pb) holds great potential for cooperative bond activation and catalysis. In this work, we investigate the reactivity of a low-coordinate Pt(0)/Ge(II) system that emerges from the reaction between the monoligated platinum(0) precursor [(PMe2ArDipp2)Pt(olefin)] with germylene dimer [ArDipp2GeCl]2 (where ArDipp2 = C6H3−2,6-(C6H3−2,6- i Pr2)2). The resulting complex reveals ability for cooperative bond activation. Stoichiometric reactions with dihydrogen, water, methanol, ammonia and alkynes unveil the formation of Pt(II)-germyl compounds, characterized by distinct isomeric forms, whose flexibility derives from the particularly low-coordination. We explore its catalytic potential in the hydrodehalogenation of aliphatic, aromatic and main-group halides under dihydrogen atmosphere using both thermal and photochemical conditions, demonstrating promising conversions even for more challenging alkyl chlorides.